Taphonomy of the middle Cambrian (Drumian) Ravens Throat River Lagerstätte, Rockslide Formation, Mackenzie Mountains, Northwest Territories, Canada. (29th July 2015) - Kimmig, Julien; Pratt, Brian R.
Abstract : The Middle Cambrian (series 3, Drumian, Bolaspidella Biozone) Ravens Throat River Lagerstätte in the Rockslide Formation of the Mackenzie Mountains, northwestern Canada, contains a Burgess Shale‐type biota of similar age to the Wheeler and Marjum formations of Utah. The Rockslide Formation is a unit of deep‐water, mixed carbonate and siliciclastic facies deposited in a slope setting on the present‐day northwestern margin of Laurentia. At the fossil‐bearing locality, the unit is about 175 m thick and the lower part onlaps a fault scarp cutting lower Cambrian sandstones. It consists of a succession of shale, laminated to thin‐bedded lime mudstone, debris‐flow breccias, minor calcareous sandstone, greenish‐coloured calcareous mudstone and dolomitic siltstone, overlain by shallow‐water dolostones of the Broken Skull Formation, which indicates an overall progradational sequence. Two ~1‐m‐thick units of greenish calcareous mudstone in the upper part exhibit soft‐bodied preservation, yielding a biota dominated by bivalved arthropods and macrophytic algae, along with hyoliths and trilobites. It represents a low‐diversity in situ community. Most of the fossils occur in the lower unit, and only the more robust components are preserved. Branching burrows are present under the carapaces of some arthropods, and common millimetre‐sized disruptions of laminae are interpreted as bioturbation. The fossiliferous planar‐laminated calcareous mudstone consists of chlorite, illite, quartz silt, calcite and dolomite and is an anomalous facies in the succession. It was deposited via hemipelagic fallout of a mixture of platform‐derived and terrestrial mud. Geochemical analysis and trace‐element proxies indicate oxic bottom waters that only occasionally might have become dysoxic. Productivity in the water column was dominated by cyanobacteria. Fragments of microbial mats are common as carbonaceous seams. Complete decay of soft tissues was interrupted due to the specific sediment composition, providing support for the role of clay minerals, possibly chlorite, in the taphonomic process.